Consumo de moda masculina: o estilo casualwear voltado para o público jovem - Prado, Nátalie Martins (2017)
A brief study of the behavior of young men aged 17-24 has made it possible to discover some of the reasons why they are trying to detach themselves from society by considering, in a generally conservative way, their own identity. Through this counterpart, a qualitative research was conducted with the target public to absorb their main tastes and customs and, take into consideration what determines the choice for a particular style of dress. After the calculation of the results, a collection of the brand "Prado" was developed to meet all the needs of the same ones that are constantly changing physical and psychic behavior during the youth phase.